Probing the intrinsic conductivity of multiwalled carbon nanotubes - Zamkov, Mikhail; Alnaser, Ali S.; Shan, Bing; Chang, Zenghu; Richard, Patrick (My University, 2006)
The authors report the two-photon electron emission study of quantum transport parameters in multiwalled carbon nanotubes. The present experimental approach is based on measurements of the electron-phonon scattering dynamics and does not employ any electrical contacts, which dramatically reduces the uncertainty in the determination of an electron mean-free path l. It is found that near the Fermi level (<0.1eV) the ballistic travel of electrons averages around 4μm, which is comparable to the nanotube length, whereas in high-current regime (⩾0.3eV) l decreases to less than 1μm.